Attributes of family physician encounters valued by older adults: a systematic review - Rebecca H. Correia; Darly Dash; Zain Pasat; Ryan P. Strum; Komal Aryal; Humayun Kabir; Maya Potter; Elaine Swayze; Pat Beaudoin; Pat Ward; Henry Yu-Hin Siu (BMC Primary Care)
Abstract Background Older adults (aged ≥ 65) are frequent users of primary care services, often presenting with unique values, needs, expectations, and preferences for family physician encounters compared to patients of younger ages. This review identified and synthesized the attributes of family physician encounters that older patients prioritize, spanning the time of accessing primary care to post-visit. Methods We conducted a systematic search of three electronic databases (MEDLINE, Ovid Embase, Web of Science) to identify peer-reviewed research articles of any design. Seven reviewers screened and extracted information using a standardized template. We narratively synthesized findings across the included studies. Older adult patient partners provided strategic input throughout the key phases of this review, including developing the research question, literature screening and synthesis, and interpreting the findings to enhance relevance and applicability. Results We identified 28,461 articles for screening after duplicate removal. Title and abstract screening resulted in 463 retained articles, with 62 articles included for analysis after full-text screening. We identified six key attributes of family physician encounters that older adults value before, during, and after visits: trust in providers, feeling heard, effective information exchange, affective behaviours, continuity of care (longitudinal relationships), and foresight/future planning. Conclusions Our findings synthesizing international evidence highlight which attributes matter most to older primary care patients as they age and increasingly access family physicians. These attributes can guide primary care planning, organization, and physician education/training to promote high-quality care for older adults. Registration Our systematic review was prospectively registered with PROSPERO (CRD42024555970).